The influence on temperature of noise, air velocity and window area during chamber tests. - Santos, Arturo Martin B.
When establishing the optimal level of an indoor climate parameter in a limited economy, there is often a cost expressed as a reduced comfort level for one or more of the other parameters. Very little knowledge currently exists regarding optimal levels when two or more parameters are linked. There is an obvious need for empirical determination of the trade off between some of these parameters. Thirty (30) heat adapted subjects participated in ten 3.5 hour exposures in climate chambers. Each subject had the option to change the air temperature in the chamber by adjusting a vote knob when prompted every five minutes. The subjects were exposed to temperature linked with each of the parameters noise, air velocity and window area in a randomized design. In a reference exposure, temperature was not linked with the other parameters. They were given instructions to optimize the climate in their respective chambers by adjusting the temperature while acknowledging the cost in one of the other parameters. During the last 15 minutes of each exposure the perceptions of subjects, skin temperatures and simple performance measures were registered. A warmer temperature was increasingly preferred when each of the parameters noise, air velocity and window area became more clearly.